2019
DOI: 10.1108/ebhrm-09-2019-0086
|View full text |Cite
|
Sign up to set email alerts
|

Global comparisons of job satisfaction across occupational categories

Abstract: Purpose Job satisfaction has positive outcomes for individuals and organizations. These include decreased turnover and conflict, increased productivity, improved work quality and creativity and innovation. Determinants entail work–life balance, advancement and development opportunities, relationships with co-workers and managers, working conditions and intrinsic and extrinsic rewards, among others. Understanding these determinants across workers and contexts is critical for effective management and the achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Past discussions outlined a consistency in the relationship between intrinsic motivation and job satisfaction [22,28,29]. A consistent positive relationship was discovered between extrinsic motivation and job satisfaction [21,28,29,31]. Various studies also noted a consistent positive relationship between job satisfaction and the intention to stay [40,42].…”
Section: Mediationmentioning
confidence: 96%
See 2 more Smart Citations
“…Past discussions outlined a consistency in the relationship between intrinsic motivation and job satisfaction [22,28,29]. A consistent positive relationship was discovered between extrinsic motivation and job satisfaction [21,28,29,31]. Various studies also noted a consistent positive relationship between job satisfaction and the intention to stay [40,42].…”
Section: Mediationmentioning
confidence: 96%
“…This theory explains that workers' motivation for professional activities impacts their performance and wellbeing. The SDT has been applied in various fields involving multiple employees, such as public employees [18,19] in the performance of green supply chain mangement [20], job satisfaction among hotel housekeepers [21], and the intention to stay among employees in the construction industry [22]. This study applied SDT to determine whether intrinsic or extrinsic factors influence women's satisfaction and desire to remain in the logistics sector.…”
Section: Self-determination Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…According to studies, on-thejob satisfaction is higher than ordinary work. Other investigations have revealed that a lot of industrial workers are unsatisfied, whereas a few specialists are dissatisfied (Andrade & Westover, 2019).…”
Section: Occupational Factorsmentioning
confidence: 99%
“…• Competencies Needed: When there is a high level of expertise, it tends to be the primary source of happiness for employees. Satisfaction with the working conditions or remuneration became dominant only when satisfaction with skill had declined significantly (Andrade & Westover, 2019).…”
Section: Occupational Factorsmentioning
confidence: 99%